A sensorless control strategy for PMSM based on high frequency square wave voltage injection at low switching frequency - DONG Shifan; JIANG Wei; WANG Xiaofan; QIU Tengfei; ZHOU Minglei; WANG Chenchen (机车电传动)
This paper presents an estimation method of rotor position at low speeds for permanent magnet synchronous motors (PMSM), using a high frequency (HF) square wave voltage injection technique at a low switching frequency. This method utilized variations in q-axis current resulting from the voltage injection to estimate rotor position errors. A Luenberger state observer was incorporated to estimate rotor position based on changes in q-axis current, along with a straightforward design principle provided for the zero and pole points of the Luenberger state observer. The experimental results show that the proposed sensorless control algorithm is effective in accurately tracking actual values in the rotor speed and position estimation at low switching frequency.